The Development of Learning Evaluation Management in Utilizing ICT Systems in Primary School Around Banda Aceh City - Hazal Fitri; Irfandi Irfandi; Murniati Murniati; Nasir Usman (BIRCU, 2019)
This research study aims to design the development of a suitable learning evaluation management model in the utilizing of the Banda Aceh Primary School Information Communication Technology (ICT) system, to develop what learning evaluation management model is suitable for utilizing Information Communication Technology (ICT) systems level of Primary School in Banda Aceh City. Then aims to improve the performance of the development of learning evaluation management models in the utilization of the Information Communication Technology (ICT) system at the Primary School level in Banda Aceh, providing a place for relatively new developing lecturers/ research groups in research capabilities to be able to utilize the facilities and expertise, and adopt and imitate a good research culture from a group of researchers who are more advanced in other universities in carrying out quality research. The program also aims to build research collaboration between universities in Indonesia. The method used in this research is development research (research and development version of Borg and Gall, 1983). The expected benefits in this research study are that all teachers who teach at the elementary school level can use / utilize the Information Communication Technology (ICT) system in the learning process, this is to improve the quality of education at that level.